Maternal Iron Deficiency and Its Effects on the Fetus and Infant - Novita Lumbanraja; Agung Ikhssani (Poltekkes Kemenkes Palembang, 2021)
Iron is essential for the function of all cells through its role in oxygen delivery, electron transport, and enzymatic activity. Cells with high metabolic rates require more iron and are at greater risk for dysfunction during iron deficiency. Iron deficiency is associated with adverse pregnancy outcomes, including increased maternal disease, low birth weight, prematurity, and intrauterine growth restriction. The rapidly developing fetal brain is particularly at risk for iron deficiency, which can occur due to maternal iron deficiency, hypertension, smoking, or glucose intolerance. Low maternal gestational iron intake is associated with autism, schizophrenia, and abnormal brain structures in the offspring. Newborns with iron deficiency have impaired recognition memory, slower processing speed, and poorer bonds that persist despite postnatal iron deficiency. Scientific sources were obtained from Google Scholar and Pubmed in the form of textbooks and scientific journals totaling 33 pieces. This literature review describes the neurocognitive and mental health consequences of fetal iron deficiency and emphasizes that fetal iron is a key nutrient influencing brain development and function throughout life